Human development in tourism spaces - Huaita Alfaro, Ana María (2017)
The current importance achieved by the tourism sector leads to the analysis of its close relationship with human development, thus complementing the classic vision of economic development applied when evaluating this sector. In this intention, the human development and capabilities approach is introduced in order to observe how it is possible to broadly meet needs in terms of human well-being from tourism. Processes and elements defining the tourism context are analysed applying the capabilities approach, and opportunities and risks to achieve enriching experiences within this context are identified. In particular, it is highlighted the importance to observe encounters between locals and visitors as well as interactions around culture as dynamics facilitating an inclusive and sustainable development..